Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
the solution is (2, -2)
Step-by-step explanation:
We'll solve this system by substitution. Set y = x - 4 = to y = 4x - 10. The result, which no longer features y, is x - 4 = 4x - 10.
First, subtract x from both sides. We get -4 = 3x - 10, or 6 = 3x. Then x = 2.
Substituting 2 for x in y = x - 4, we get y = 2 - 4, or y = -2.
Then the solution is (2, -2).
Answer:
y=-2
x=2
Step-by-step explanation:
If y=x-4, that means x is 4 larger than y.
y=4x-10
If y is 2 and x is 6 (2≠24-10) or (2≠14)
If y is 1 and x is 5 (1≠20-10) or (1≠10)
If y is 0 and x is 4 (0≠16-10) or (0≠6)
The pattern is that each time y and x goes 1 down, the difference between y and x goes down 3 each time. So if you keep on going down in the negatives,
If y is -2 and x is 2 (-2=8-10) or (-2=-2)
I would appreciate it if you pick this answer (It'll be my first one)
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.